Efficacy and safety of pamapimod in patients with active rheumatoid arthritis receiving stable methotrexate therapy. Issue 2 (8th April 2009) - Alten, R E; Zerbini, C; Jeka, S; Irazoque, F; Khatib, F; Emery, P; Bertasso, A; Rabbia, M; Caulfield, J P
Abstract : Objective: To determine the efficacy and safety of pamapimod in adult patients with active rheumatoid arthritis (RA) who had an inadequate clinical response to methotrexate (MTX). Methods: Patients receiving stable doses of MTX were randomised to one of six dose groups and received 12 weeks of double-blind pamapimod (up to 300 mg once daily) or matching placebo. The primary efficacy measure was the proportion of patients with ⩾20% improvement in RA based on the American College of Rheumatology criteria (ACR20) at 12 weeks. Secondary measures were ACR50, Disease Activity Score (DAS)/European League Against Rheumatism (EULAR) responses and the individual ACR core set of parameters. Safety measures included adverse events (AEs), laboratory testing and immunology assessments. Results: On a background of MTX, the percentage of patients with an ACR20 response at week 12 in the pamapimod groups (31% to 43%) was not significantly different from placebo (34%). Secondary efficacy end points showed a similar pattern. AEs were typically mild and included infections, gastrointestinal disturbances, dizziness and rashes; AEs resulting in discontinuation of study drug were primarily attributed to infections. Conclusion: In patients with active RA receiving stable doses of MTX, pamapimod showed non-significant improvement in efficacy outcomes compared to placebo.